Case Report: Multisystem Langerhans Cell Histiocytosis (LCH) and Myelodysplastic Syndrome (MDS) in a 13-Month-Old Female - Dian Sukma Hanggara; Desyi Desyi (Jurnal Kedokteran Brawijaya, 2021)
Langerhans Cell Histiocytosis or LCH and Myelodysplastic syndrome or MDS in children are rare diseases. It is estimated to be 1 to 4 cases per 1 million population and less than 5% of hematologic cases. MDS in LCH can occur due to genetic predisposition, impaired cytokine production, or secondary to chemotherapy.Â  The article reported a patient case of a 13-month-old female who came to hospital with paleness since two weeks before admission. The patient also experienced skin redness, abdominal distention, and weight loss. From the physical examination, anemia, maculopapular rash, and hepatosplenomegaly were obtained. From the laboratory test, anemia of hypochromic anisopoikilocytosis, monocytosis, thrombocytopenia, and hypoalbuminemia were obtained. On examination of bone marrow aspiration, MDS with Refractory Cytopenia of Childhood type or RCC was obtained. Positive results confirmed the diagnosis of Langerhans Cell Histiocytosis on CD68 and S100 in histopathological examinations.